High-performance palmityl palmitate phase change microcapsules for thermal energy storage and thermal regulation. (1st July 2023) - Lu, Wei; Yu, Anqi; Dong, Hao; He, Zhenglong; Liang, Yuntao; Liu, Weitao; Sun, Yong; Song, Shuanglin
Abstract: Phase change microcapsules, which feature high latent heat and stability and can well mix with epoxy resin substrates, were synthesized through the solvent-free interfacial polymerization method with palmityl palmitate as the core material and low-toxicity dicyclohexylmethane 4, 4′-diisocyanate as the shell material. The synthesized microcapsules were characterized by multiple techniques. The performances of microcapsules at different core-shell ratios were compared, and the applicabilities of epoxy resins with different contents of optimal microcapsules were investigated. Results show that, at a core-shell ratio of 16:4, the synthesized microcapsules achieve an encapsulation rate of 84.47%, and their enthalpies of melting and crystallization reach 218.49 J/g and 219.72 J/g, respectively. Moreover, the microcapsules exhibit outstanding thermal stability and reliability. They can remain intact without leakage after heating at 150 °C for 2 h, and their enthalpies of melting and crystallization can remain over 196.58 J/g and 202.23 J/g after 500 heating and cooling cycles. In addition, the microcapsules can uniformly disperse in epoxy resin, significantly influencing its heat transfer property and temperature regulation ability. With a 15% microcapsule content, the epoxy resin has a reduced thermal conductivity of 0.5834 W/mK, with delays of 76.0% and 51.4% in the time used for the temperature rise/fall process. Graphical abstract: Image 1 Highlights: One-pot method was used to prepare palmityl palmitate microcapsules. The microcapsules achieve a high latent heat capacity over 218 J/g. The microcapsules show excellent thermal stability, reliability and applicability. The microcapsules exhibit potential for enhancing thermal regulation. The microcapsules can promote the toughness of epoxy resin materials.